1999
DOI: 10.1016/s0022-5223(99)70437-x
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning attenuates postischemic coronary artery endothelial dysfunction in a model of minimally invasive direct coronary artery bypass grafting

Abstract: In this minimally invasive direct coronary artery bypass grafting model, both agonist-stimulated and basal postischemic endothelial dysfunction were attenuated by ischemic preconditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…129 Another study in dogs with 60-minute coronary occlusion and reperfusion also reported no improvement in the coronary vasodilator response to acetylcholine but improved reflow with ischemic preconditioning by 2 cycles of 5-minute myocardial ischemia/5-minute reperfusion. 130 However, the majority of subsequent studies reported protection by ischemic preconditioning on endothelial function, as assessed by endotheliumdependent coronary vasodilation in response to acetylcholine, serotonin, or ADP in rats, [131][132][133] guinea pigs, 134 dogs, 135,136 pigs, 137 and goats. 138 Mechanistically, the preservation of endothelial function by ischemic preconditioning was related to adenosine, 132,136 bradykinin, 133 and nitric oxide.…”
Section: Coronary Vascular Protection By Ischemic Preconditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…129 Another study in dogs with 60-minute coronary occlusion and reperfusion also reported no improvement in the coronary vasodilator response to acetylcholine but improved reflow with ischemic preconditioning by 2 cycles of 5-minute myocardial ischemia/5-minute reperfusion. 130 However, the majority of subsequent studies reported protection by ischemic preconditioning on endothelial function, as assessed by endotheliumdependent coronary vasodilation in response to acetylcholine, serotonin, or ADP in rats, [131][132][133] guinea pigs, 134 dogs, 135,136 pigs, 137 and goats. 138 Mechanistically, the preservation of endothelial function by ischemic preconditioning was related to adenosine, 132,136 bradykinin, 133 and nitric oxide.…”
Section: Coronary Vascular Protection By Ischemic Preconditioningmentioning
confidence: 99%
“…138,139 The preservation of endothelial function by ischemic preconditioning became apparent not only as improved endothelium-dependent coronary vasodilation but also as reduced leukocyte adherence. 134,135,139 Coronary endothelial function recovers only slowly after myocardial ischemia/reperfusion and is still depressed after 1 month, but ischemic preconditioning also improves endothelium-dependent coronary vasodilation in response to acetylcholine and endothelial ultrastructure after 1 month. 140 Vice versa, delayed ischemic preconditioning 24 hours before the sustained myocardial ischemia/reperfusion increases the activity of endothelial nitric oxide synthase, which mediates preservation of coronary vasodilator response to acetylcholine, carbachol, and bradykinin.…”
Section: Coronary Vascular Protection By Ischemic Preconditioningmentioning
confidence: 99%
“…Therefore, IP might be an ideal and effective method in achieving additional myocardial protection. There are nevertheless controversial data in various studies [1,[98][99][100]. During minimal invasive CABG operation, Jacobsohn described the protective effect of IP, even no change in ST-T segment and T-wave during IP has an IP effect of improved contractility [40].…”
Section: Off-pump Cabg Patientsmentioning
confidence: 99%
“…This can be explained by an upregulation of coronary vascular NO production, potentially involved in the mechanism of the delayed window of preconditioning [51]. Thourani et al using the left circumflex artery as a control found that in the previously ischemic vascular bed of the anterior vascular descending artery the vasodilatory response to acetylcholine is impaired [52]. If the occlusion is preceded by the ischemic preconditioning no significant difference in the response is observed between the vascular beds of the two arteries.…”
Section: Shear Stress and Endothelial Cell Dys-functionmentioning
confidence: 99%